THE ROLES OF INTERPERSONAL RELATIONSHIP IN MANAGING BUSINESS RELATIONSHIP IN A HIGH-RISK AND UNCERTAIN MARKET - Sulhaini Saadi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2010)
This paper aims to explore the roles of interpersonal relationship in managing business relationship in a high-risk and uncertain market. Exporting to a high-risk and uncertain market can lead to a greater possibility of problems occurring; such problems include: not receiving payment due to poor local banking systems; issues with tenders due to political uncertainty, and other problems. Managing business relationships in such markets can be more complex and difficult, exporters have to find ways to overcome the problems. The study followed the traditions of inductive logic and used a qualitative approach by exploring experiences of a small number case of British firms exporting to the Indonesian market. Data was analysed following the procedure of General Inductive Approach (GIA). The finding suggests that interpersonal relationships have greater roles as communication channels, the key mechanism to solve problems and to strengthen interpersonal and organisational trust to reduce perception of risk and uncertainty associated with the market and the business relationship.